How demanding is the revealed preference approach to demand? - Timothy K. M. Beatty; Ian A. Crawford (Centre for Microdata Methods and Practice (cemmap), 2010)
A well known problem with revealed preference methods is that when data are found to satisfy their restrictions it is hard to know whether this should be viewed as a triumph for economic theory, or a warning that these conditions are so undemanding that almost anything goes. This paper allows researchers to make this distinction. Our approach builds on theoretical support in the form of an axiomatic cardinal characterisation of a measure of predictive success due to Selten (1991). We illustrate the idea using a large, nationally representative panel survey of Spanish consumers with broad commodity coverage. The results show that this approach to revealed preference methods can lead us radically to reassess our view of the empirical performance of economic theory.
Keywords: 330; Konsumentenverhalten; Offenbarte Präferenzen; Prognose; Spanien; Theorie